Polyphenols: Inflammation - Natsume, Midori (Current Pharmaceutical Design, 2018)
Background: Polyphenols widely distributed in plants, fruits and vegetables have received considerable attention on account of their physiological functions, including their antioxidant and anti-inflammatory properties. Some antioxidant components of cacao liquor prepared from fermented and roasted cacao beans, which is a major ingredient of cocoa and chocolate products, have been characterized as flavan-3-ols and procyanidin oligomers. Methods: This review focuses on a specific group of (-)-epicatechins and their oligomers, the procyanidins, in cacao products. Dietary polyphenols in cacao products have been shown to reduce hypertension, reduce platelet aggregation, improve serum lipids, and lower the incidence of atherosclerosis in animal studies and clinical trials. Conclusion: The intake of cacao products reduces hypertension and atherosclerosis on account of their physiological functions as antioxidants and anti-inflammation agents, indicating the mechanisms of prevention of hypertension and atherosclerosis by polyphenols.
Keywords: cacao